One Pot Synthesis of N-acetylglycine from N-acetyl Glucosamine over Bifunctional Ag/MgO - Dianwen Qi; Qingya Cao; Chenxi Huang; Xueying Qi; Chongzhou Wang; Jinhang Dai (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The catalytic conversion of chitin biomass provides an environment-friendly approach for the synthesis of valuable organonitrogen compounds. Here, we prepared bifunctional Ag/MgO by simple deposition-precipitation method. The catalysts exhibited good catalytic activity for one pot synthesis of N-acetylglycine (AcGly) from N-acetyl glucosamine (NAG), offering a 26.2% yield under optimized conditions. The basic nature of MgO contributed to the retro-aldol of NAG, and Ag species catalyzed the oxidation of intermediate to AcGly. The spent catalyst could be recycled and reused for NAG conversion to AcGly. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).